The current distribution and threats of some small mammals with high conservation value from the orders Eulipotyphla, Chiroptera and Rodentia in Vietnam - Truong Nguyen, Son; V. Kruskop, Sergei; Dinh Vu, Thong; Lý Ngọc, Tú; Óhida, Tatsuo; Endo, Hideki; Motokawa, Masaharu; Tuan Bui, Hai (Academia Journal of Biology, 2024)
Vietnam is recognized as one of the world's biodiversity hotspots. Recent studies have uncovered numerous new mammal species, highlighting the significant biodiversity of Vietnam not only within the region but globally. However, these new species, along with established ones, are currently affected by climate change and human activities, which have led to the decline of certain populations and placed some species at risk of extinction. Since 2001, our surveys and assessments of the current status and distribution of small mammals from the orders Eulipotyphla, Chiroptera, and Rodentia have identified 48 species that are prioritized for conservation with varying conservation levels based on their actual status, especially those with less individual numbers in population, narrow distribution ranges, and those still affected by human activities. The research has identified 17 priority sites for habitat conservation, including two in the Northeast, three in the Northwest, four in the North Central region, three in the Central Highlands, and five in the Mekong Delta.